The Influence Of Customer Perceived Ethicality And Brand Trust On Purchase Intention At The Body Shop Indonesia - Khairani, Nur Aulia; Lubis, Arlina Nurbaity; Sembiring, Beby Karina Fawzeea (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to analyze the influence of Customer Perceived Ethicality (CPE) and Brand Trust on Purchase Intention among The Body Shop Indonesia consumers. The ethical and sustainability-based beauty industry is growing, but there is still a research gap regarding the extent to which consumer ethical perceptions of brands and brand trust influence purchase intentions in the Indonesian market, especially amidst increasing consumer awareness of environmental and social issues. This study uses a quantitative approach with a survey method of 200 respondents who are The Body Shop Indonesia consumers in the Medan area. The sampling technique uses purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS 4.0 software. The results show that Customer Perceived Ethicality has a positive and significant effect on Purchase Intention (beta = 0.412; p < 0.001), and Brand Trust has a positive and significant effect on Purchase Intention (beta = 0.358; p < 0.001). Simultaneously, CPE and Brand Trust are able to explain 54.3% of the variance in Purchase Intention. These findings imply that companies need to consistently communicate ethical commitments and build strong brand trust to drive consumer purchase intentions.